Conserved immunogenic peptides of Ebola glycoprotein elicit immune response in human peripheral blood mononuclear cells. (31st August 2021) - Jain, Sahil; Baranwal, Manoj
Abstract: In the past 45 years, ebolaviruses have periodically caused epidemics on the African continent. In December 2019, approval of a recombinant vector‐based EBOV vaccine, named Ervebo, came as encouraging news; still, there is a long way to go in the development of an accessible, global, and pan‐ebolavirus vaccine. The current study expanded our previous in silico work which was conducted on ebolavirus glycoprotein and this resulted in the identification of three potentially immunogenic peptides (P1 – FKRTSFFLWVIILFQRTFSIPL, P2 – LANETTQALQLF, and P3 – RATTELRTFSILNRKAIDF). An analysis to estimate the number of expected human leukocyte antigen (HLA) responders revealed that P1, P2, and P3 can potentially interact with 2540, 2150, and 2802 HLA alleles, respectively. Further, these peptides were subject to in vitro analysis wherein the human peripheral blood mononuclear cell proliferation and interferon‐gamma (IFN‐γ) production by peptide stimulated cells was studied in 10 healthy human blood samples with the help of a 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide (MTT) assay and a sandwich enzyme‐linked immunosorbent assay (ELISA) respectively. P3 presented the best results, a significant ( P < 0.05) peptide induced cell proliferation and IFN‐γ stimulation for 8 and 10 samples, respectively, followed by P1 (5 and 6) and P2 (5 and 7). The in silico and in vitro results obtained in this study indicate the immunogenic potential of these peptides and warrant exploration of the effects on other cytokines as well as in vivo experimental validation.